Inflammatory Signatures of Pathogenic and Non-Pathogenic Leptospira Infection in Susceptible C3H-HeJ Mice - Shetty, Advait; Kundu, Suman; Gomes-Solecki, Maria (Frontiers in Cellular and Infection Microbiology, 2021)
The exact global impact of leptospirosis is unknown due to inadequate surveillance systems in place in most low-income countries. In this study we analyzed the differences in mouse inflammatory signatures involved in pathogenic versus non-pathogenic Leptospira recognition at 24h and 72h post infection. Injection of C3H-HeJ mice with non-pathogenic L. biflexa increased circulation of a few chemokines (5/21, 24%) without secretion of cytokines in blood that resulted in engagement of resident macrophages, dendritic cells, neutrophils and NK cells without engagement of T cells. In contrast, pathogenic L. interrogans induced circulation of a much higher panel of chemokines (18/21, 86%) and pro- and anti-inflammatory cytokines (11/19, 58%) in blood with a resulting signaling cascade leading to engagement of macrophages, dendritic cells, monocytes, NK cells and T cells without engagement of neutrophils. Although neutrophils do not appear to be engaged, a considerable number of chemokines that recruit other granulocytes such as eosinophils and basophils were also increased at 72h post infection with L. interrogans. Overall, the data suggest that prevention of dissemination of L. biflexa is associated with an early engagement of the innate immune response characterized by upregulation of a few chemokines that results in an efficacious phagocytic response without an overwhelming increase of pro-inflammatory cytokines. However, when macrophages fail to clear a pathogenic serovar such as L. interrogans, the adaptive response (T cells) is engaged to help out, but the resulting chemo-cytokine storm mediates a robust but non-resolving inflammatory response to pathogenic Leptospira that results in dissemination, kidney colonization, pathology and disease.